Necropolitics and Culture; or the Embedding of Cultural Practices in Necropower. - SANTIÁÑEZ, NIL (University of Toronto Quarterly)
In the burgeoning field of necropolitical studies, priority has been given to the exploration of material practices. Culture is generally regarded either as secondary to these practices or as a set of mimetic representations of necropolitics. In contrast to such approaches, this article contends that the critical gaze ought to be directed at necropower's production of cultural artifacts meant to achieve necropolitical goals. A theory of necropolitics that does not encompass the necropolitical production and manipulation of culture is insufficient for it fails to give a complete and thorough account of the complex and variegated technologies of necropower. Cultural practices are much more than simple representations of necropolitics or their ideological or theoretical substratum; they also have the ability to subjugate life to the power of death by actively participating in the construction of death-worlds. This thesis is demonstrated by means of an analysis of the interconnection between necropolitics and culture in General Franco's Spain (1939-75)· The adoption of the theoretical standpoint put forth in this article might refine and broaden the field of necropolitical studies. Discussions on necropolitics need to open up to the embedding of culture in necropower. Centred on the analysis of the role of cultural practices within necropolitics, this direction might prove fruitful in future studies for it would reveal, with more precision than the studies limited to analysing the material dimension of necropolitics, the extent, the force, the tools, and the power of coercion of the politics of death.